ToxopJasmagondaNia JLLE AND MANCEAUX PADA AYAM BUKAN RAS (Gallus sp.) DAN BURUNG MERPATI (Columba Una Gmelin) DIKOTAMADYA BOGOR - L.E Setyorini; E. Purwaningsih; S. Hartini; J. Aziz (BERITA BIOLOGI, 1998)
Using Indirect Hemqiglutination (IHA) test on 26 domesticfowl (Gallus sp.)and domestic pigeon (Columba liviaj were screened "Toxoplasrna gondii infection.All of the serum samples tested were positiffor this protopal infection.From the quantitatif test on 14positives serum samples, 14,28 % has the lowest liter of1Â£4 and 7,14 % has the highest liter of 1:1024. Mode of the disease spreading and the prevention off.gondii were discussed.